Dispersion of carbon dioxide bubble release from shallow subsea carbon dioxide storage to seawater - Pham, L.H.H.P. (Elsevier Ltd, 2020)
A large amount of carbon dioxide (CO2) gas injected into shallow reservoirs of carbon capture and storage (CCS) system could be hazardous to marine life if the CO2 released through the seabed. Effective dispersion model is required to assess the realistic exposure as it affects the partial pressure of CO2 and pH of seawater. Here, the development of the dispersion model based on CFD FLUENT that integrates chemical reaction of CO2 bubble in seawater plume is discussed. The capability of the developed model has been demonstrated through a comparison of simulation results with published small-scale field experimental data. Parametric simulation has been conducted to investigate the impact of release rate, current velocity and release size on the dispersion of CO2 gas-seawater. The study confirmed that high release rate in low tide (and low current) condition has the most severe impact. Â© 2020 Elsevier Ltd